HOMESCHOOLING SEBAGAI MODEL PENDIDIKAN PEMBEBASAN - Hariyanto, Erie (KARSA: Journal of Social and Islamic Culture)
AbstractHomeschooling is a typeÂ  of optional education concept that is managed by parent. The instructional process must facilitate the development of studentâ€™s unique potency. In the process of homeschooling, parents are free to select the curriculum, learning materials, and evaluation as they want. In Indonesia, it has a strong and legal basic and it appears as one of the potencies of eduactional model diversity that occurs in social life to realize an educationa liberation. Kata-kata kuncihomeschooling, pendidikan, pembebasan, anak didik